2017
DOI: 10.1136/bjophthalmol-2017-310975
|View full text |Cite
|
Sign up to set email alerts
|

Blepharitis as an early sign of metabolic syndrome: a nationwide population-based study

Abstract: Blepharitis is significantly related to MetS and can serve as an early sign of MetS. Additional studies should examine the relationship between blepharitis and MetS in terms of severity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
4
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 24 publications
(19 reference statements)
0
4
0
1
Order By: Relevance
“…In our study, blepharitis was observed in 23.7% of patients, whereas MGD was observed in 53.75% of patients. Lee et al [ 30 ] stated that blepharitis is significantly related to metabolic syndromes such as DM, and can serve as an early sign of DM. Hom et al [ 31 ] and Ansari et al [ 32 ] observed similar results in their studies.…”
Section: Discussionmentioning
confidence: 99%
“…In our study, blepharitis was observed in 23.7% of patients, whereas MGD was observed in 53.75% of patients. Lee et al [ 30 ] stated that blepharitis is significantly related to metabolic syndromes such as DM, and can serve as an early sign of DM. Hom et al [ 31 ] and Ansari et al [ 32 ] observed similar results in their studies.…”
Section: Discussionmentioning
confidence: 99%
“…V indikaci diet se dnes zdá, že nejlepší dietou na metabolický syndrom je konzumace vlákniny [8]. A to, že metabolický syndrom má vazbu na jakékoli zánětlivé onemocnění, ukazují dnes 2 práce o blefaritidě [9,10]. I tak malý zánět z hlediska celotělového, jako jsou záněty oka, mají k metabolickému syndromu vztah.…”
Section: Další Pohledy Na Metabolický Syndromunclassified
“…Patients with posterior blepharitis have inflammation of the posterior lid margin involving the meibomian gland, and this form is often associated with several systemic diseases ( 1 , 3 ). An observational study published in 2013 revealed that MGD was significantly associated with increased systemic total cholesterol and low-density lipoprotein (LDL) levels, and another population-based study reported an aHR of 1.145 for an increased risk of developing metabolic syndrome in patients with blepharitis ( 15 , 16 ). Meibomian secretions of meibum are composed of a mixture of lipids, including wax esters, cholesteryl esters, cholesteryl esters of (O-acyl)-ω-hydroxy fatty acids, triacylglycerols, free fatty acids, cholesterol and small amounts of polar and non-polar lipids ( 17 ).…”
Section: Discussionmentioning
confidence: 99%
“…However, the use of statin was able to decrease the risk of blepharitis in patients with DM (aHR:0.757, p = 0.001). In a population study assessing blepharitis as a potential indicator for metabolic syndrome, hypertension and DM were not correlated with blepharitis ( 16 ). However, a study by Nemet et al and another population-based study reported a significant association of cardiovascular disease, including hypertension and coronary heart disease, with blepharitis ( 22 , 25 ), which is consistent with our results.…”
Section: Discussionmentioning
confidence: 99%